Analyzing the Antecedents of Duty Free Consumption Behavior - Gavish, Yossi; Shoham, Aviv (Advances in Social Sciences Research Journal, 2019)
Consumers’ duty free shopping represents an under-researched consumption behavior with far reaching economic and marketing implications. This study explores the extent to which personality trait impulsiveness, shopping enjoyment, and price prestige, mediated by shopping involvement and the perception of duty free shops influences buying intentions and actual buying in duty free shops. A convenience sample of 196 Israeli adults inIsrael’s Ben-Gurion International airport was used. A structural equation model was used to analyze the relationships among the model’s variables. The model supports the positive impact of trait impulsiveness, shopping enjoyment, and price prestige on shopping involvement and perception of duty free shops. In addition, shopping involvement and duty- free shops perception enhanced buying intentions, which, in turn, increased several indicators of actual buying behavior. This paper contributes to the socio-psychology and marketing literatures by developing and testing an integrative model. It further provides implications for marketing managers and salespeople.